Neuroimaging in encephalitis: analysis of imaging findings and interobserver agreement. Issue 10 (October 2016) - Granerod, J.; Davies, N.W.S.; Mukonoweshuro, W.; Mehta, A.; Das, K.; Lim, M.; Solomon, T.; Biswas, S.; Rosella, L.; Brown, D.W.G.; Crowcroft, N.S.; ,; et al.
Abstract : Aim: To assess the role of imaging in the early management of encephalitis and the agreement on findings in a well-defined cohort of suspected encephalitis cases enrolled in the Prospective Aetiological Study of Encephalitis conducted by the Health Protection Agency (now incorporated into Public Health England). Materials and methods: Eighty-five CT examinations from 68 patients and 101 MRI examinations from 80 patients with suspected encephalitis were independently rated by three neuroradiologists blinded to patient and clinical details. The level of agreement on the interpretation of images was measured using the kappa statistic. The sensitivity, specificity, and negative and positive predictive values of CT and MRI for herpes simplex virus (HSV) encephalitis and acute disseminated encephalomyelitis (ADEM) were estimated. Results: The kappa value for interobserver agreement on rating the scans as normal or abnormal was good (0.65) for CT and moderate (0.59) for MRI. Agreement for HSV encephalitis was very good for CT (0.87) and MRI (0.82), but only fair for ADEM (0.32 CT; 0.31 MRI). Similarly, the overall sensitivity of imaging for HSV encephalitis was ∼80% for both CT and MRI, whereas for ADEM it was 0% for CT and 20% for MRI. MRI specificity for HSV encephalitis between 3–10 days after symptom onset was 100%. Conclusion: There is a subjective component to scan interpretation that can have important implications for the clinical management of encephalitis cases. Neuroradiologists were good at diagnosing HSV encephalitis; however, agreement was worse for ADEM and other alternative aetiologies. Findings highlight the importance of a comprehensive and multidisciplinary approach to diagnosing the cause of encephalitis that takes into account individual clinical, microbiological, and radiological features of each patient. Highlights: We assessed the role of imaging in encephalitis. We assessed the agreement between raters on scan interpretation. Diagnosis for herpes simplex encephalitis (HSE) was good. Agreement was worse for ADEM and other alternative aetiologies. HSE can be dismissed if MRI normal 72 hours after neurological symptom onset (with negative CSF tests).